The Application of Leaf Ultrasonic Resonance to Vitis vinifera L. Suggests the Existence of a Diurnal Osmotic Adjustment Subjected to Photosynthesis - Sancho-Knapik, Domingo; Medrano, Hipólito; Peguero-Pina, José J.; Mencuccini, Maurizio; Fariñas, Maria D.; Álvarez-Arenas, Tomás G.; Gil-Pelegrín, Eustaquio (Frontiers in Plant Science, 2016)
The main objective of this study was to apply the air-coupled broad-band ultrasonic spectroscopy in attached transpiring leaves of Vitis vinifera L. to monitor changes in leaf water potential (Y) through the measurements of the standardized value of the resonant frequency associated with the maximum transmitance (f/fo). With this purpose, the response of grapevine to a drought stress period was investigated in terms of leaf water status, ultrasounds, gas exchange and sugar accumulation. Two strong correlations were obtained between f/fo and Y measured at predawn (pd) and at midday (md) with different slopes. This fact implied the existence of two values of Y for a given value of f/fo, which was taken as a sign that the ultrasonic technique was not directly related to the overall Y, but only to one of its components: the turgor pressure (P). The difference in Y at constant f/fo (d) was found to be dependent on net CO2 assimilation (A) and might be used as a rough estimator of photosynthetic activity. It was then, the other main component of Y, osmotic potential (π), the one that may have lowered the values of midday Y with respect to predawn Y by the accumulation of sugars associated to net CO2 assimilation. This phenomenon suggests the existence of a diurnal osmotic adjustment in this species associated to sugars production in well-watered plants.